Determining the optimal threonine:lysine ratio for the 25 to 50 lb pig - Bergstrom, J.R.; Loughmiller, J.A.; Musser, R.E.; Nessmith, W.B.Jr.; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 21-day growth trial was conducted to determine the threonine: lysine ratio necessary to optimize growth performance of the 25 to 50 Ib pig reared in a high-health, segregated early-weaning (SEW) system. Ten experimental diets, including two levels of lysine (.75% and 1.10% apparent digestible lysine) and five apparent digestible threonine:lysine ratios (40, 47.5, 55, 62.5, and 70%), were used in a 2 x 5 factorial arrangement. Growth performance was improved by feeding 1.10% rather than.75% digestible lysine. Also, results indicated that the apparent digestible threonine requirement for the SEW:-reared, 25 to 50 lb pig is approximately 55% of digestible lysine.
Keywords: Swine; Early-weaned pigs; Amino acids; Threonine